In vitro and in vivo study on the osseointegration of BCP‐coated versus uncoated nondegradable thermoplastic polyurethane focal knee resurfacing implants. Issue 8 (2nd July 2020) - Jeuken, Ralph M.; Roth, Alex K.; Peters, Marloes J.M.; Welting, Tim J.M.; van Rhijn, Lodewijk W.; Koenen, Jac; Peters, Ruud J.R.W.; Thies, Jens C.; Emans, Pieter J.
Abstract: Focal knee resurfacing implants (FKRIs) are intended to treat cartilage defects in middle‐aged patients. Most FKRIs are metal‐based, which hampers follow‐up of the joint using magnetic resonance imaging and potentially leads to damage of the opposing cartilage. The purpose of this study was to develop a nondegradable thermoplastic polyurethane (TPU) FKRI and investigate its osseointegration. Different surface roughness modifications and biphasic calcium phosphate (BCP) coating densities were first tested in vitro on TPU discs. The in vivo osseointegration of BCP‐coated TPU implants was subsequently compared to uncoated TPU implants and the titanium bottom layer of metal control implants in a caprine model. Implants were implanted bilaterally in stifle joints and animals were followed for 12 weeks, after which the bone‐to‐implant contact area (BIC) was assessed. Additionally, 18F‐sodium‐fluoride (18F‐NaF) positron emission tomography PET/CT‐scans were obtained at 3 and 12 weeks to visualize the bone metabolism over time. The BIC was significantly higher for the BCP‐coated TPU implants compared to the uncoated TPU implants ( p = .03), and did not significantly differ from titanium ( p = .68). Similar 18F‐NaF tracer uptake patterns were observed between 3 and 12 weeks for the BCP‐coated TPU and titanium implants, but not for the uncoated implants. TPU FKRIs with surface modifications could provide the answer to the drawbacks of metal FKRIs. Abstract : Focal knee resurfacing implants (FKRIs) are intended to treat cartilage defects in middle‐aged patients. Most FKRIs are metal‐based, which hampers follow‐up of the joint using magnetic resonance imaging and potentially leads to damage of the opposing cartilage. The purpose of this study was to develop a nondegradable thermoplastic polyurethane (TPU) FKRI and investigate its osseointegration. Different surface roughness modifications and biphasic calcium phosphate (BCP) coating densities were first tested in vitro on TPU discs. The in vivo osseointegration of BCP‐coated TPU implants was subsequently compared to uncoated TPU implants and the titanium bottom layer of metal control implants in a caprine model. Implants were implanted bilaterally in stifle joints and animals were followed for 12 weeks, after which the bone‐to‐implant contact area (BIC) was assessed. Additionally, 18F‐sodium‐fluoride (18F‐NaF) positron emission tomography PET/CT‐scans were obtained at 3 and 12 weeks to visualize the bone metabolism over time. The BIC was significantly higher for the BCP‐coated TPU implants compared to the uncoated TPU implants (p = .03), and did not significantly differ from titanium (p = .68). Similar 18F‐NaF tracer uptake patterns were observed between 3 and 12 weeks for the BCP‐coated TPU and titanium implants, but not for the uncoated implants. TPU FKRIs with surface modifications could provide the answer to the drawbacks of metal FKRIs.